Changing paradigms in sinus and skull base surgery as the COVID‐19 pandemic evolves: Preliminary experience from a single Italian tertiary care center - Karligkiotis, Apostolos (Head Neck, 2020)
BACKGROUND: Italy was the first European country suffering from COVID‐19. Health care resources were redirected to manage the pandemic. We present our initial experience with the management of urgent and nondeferrable surgeries for sinus and skull base diseases during the COVID‐19 pandemic. METHODS: A retrospective review of patients treated in a single referral center during the first 2 months of the pandemic was performed. A comparison between the last 2‐month period and the same period of the previous year was carried out. RESULTS: Twenty‐four patients fulfilled the inclusion criteria. A reduction of surgical activity was observed (−60.7%). A statistically significant difference in pathologies treated was found (P = .016), with malignancies being the most frequent indication for surgery (45.8%). CONCLUSIONS: Although we feel optimistic for the future, we do not feel it is already time to restart elective surgeries. Our experience may serve for other centers who are facing the same challenges.